Post-Graduation Transitions of International Students in Taiwan: Barriers to Labour Market Integration - Mukhamad Zulianto; Irmadatus Sholekhah; Badrus Sholeh; Rofiq Noorman Haryadi; Sujadmi Sujadmi; Olivia Winda Ony Panjaitan (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
Taiwan has emerged as a regional education hub, drawing international students particularly from Southeast and South Asiathrough proactive recruitment and policy tools, such as the New Southbound Policy. After graduation, many of these students face substantial barriers to integrating into Taiwan’s labor market. This study particularly targets barriers to employment that international graduates face after completing their degrees, focusing on the prevailing work governance structures and systemic frameworks. This qualitative study, based on 20 in-depth interviews and policy analysis. Findings reveal that entrenched bureaucratic hurdles, racialized labor hierarchies, and structural discrimination inhibit international graduates’ access to meaningful employment. The study calls for policy realignments that reframe international graduates as long-term socio-economic assets, not transient learners.